Performance of potential distribution of CSDG MOSFET using evanescent-mode analysis - A.Maduagwu, Uchechukwu; M.Srivastava, Viranjay (International Journal of Engineering and Technology, 2019)
In nanotechnology, to overcome the restriction on the scaling (sizing) of the MOSFET, a cylindrical structure of MOSFET is suitable. It increases the switching speed (at Radio Frequency level), current flow (Double traditional MOSFET), and packaging density (billions of transistors per unit area). In this research work, analytical 2D model for potential distribution of Cylindrical Surrounding Double-Gate (CSDG) MOSFET has been derived, based on 2D Poisson solution using Evanescent-Mode analysis. The impact of Short Channel Effects (SCEs) on the channel potential has been evaluated which is based on the device parameters such as channel length, drain to source bias voltage, silicon thickness, and oxide thickness. Also, the derived closed-form expressions surface potential for both the inner and outer gate of the CSDG MOSFET produced a relatively the same results. The accuracy has been validated through the simulation analysis.Â Â Â
Keywords: CSDG MOSFET; 2D analysis; Potential Distribution; Microelectronics; Nanotechnology; VLSI.